Phase transfer of oleic acid capped NicoreAgshell nanoparticles assisted by the flexibility of oleic acid on the surface of silver - Bala, Tanushree; Swami, A.; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Colloid and Interface Science, 2005)
The phase transfer protocols in vogue for the oleic acid capped silver nanoparticles, viz., salt-induced precipitation and redispersion or phosphoric acid-induced method, are examined and compared thoroughly. A comprehensive evaluation with respect to the mechanistic aspects involved is made and the merits and demerits of the different procedures are delineated. It is found that the salt-induced precipitation and redispersion is more versatile in that the precipitate can actually be redispersed in both aqueous and organic media. However, in terms of mechanism both the routes seem to be very similar wherein the orientational change of oleic acid on the silver surface in the two different environments-organic and aqueous-plays a crucial role in the adaptability of the system to the different environments. Subsequently, this change of orientation of oleic acid on silver surface in aqueous and organic media has been utilized to phase transfer Ni-based nanoparticulate systems. The nascent oleic acid-capped Ni nanoparticles, which were synthesized by a foam-based protocol, were dispersible in water but not in nonpolar organic media such as cyclohexane or toluene. Then, just by coating a thin shell of silver on them we could achieve complete phase transfer of the NicoreAgshell from aqueous to organic media following similar procedures used for oleic acid-capped silver nanoparticles. Here, the phase transfer seems to be facilitated by the orientational flexibility of oleic acid on the silver surface as opposed to other metal surfaces as evidenced from the infrared and thermogravimetric analyses of oleic acid-capped Ni and NicoreAgshell nanoparticles. This orientation-assisted phase transfer method could be generalized and can be adapted to other systems where, if the nascent nanoparticles cannot be phase transferred as is, they can be coated by a silver shell and oleic acid making them suitable for dispersion in both aqueous and organic media. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: (1) HNMR; FTIR; Phase transfer; transmetalation core-shell nanoparticles; UV-Vis